Implementation of Inquiry Learning Model with STEM Approach to Improve Student Science Literacy in Environmental Pollution Materials - Aulia Rahman (Universitas Tidar, 2023)
The study aims to improve the learning process that has been carried out with the aim of increasing students' scientific literacy on environmental pollution topic using the inquiry learning model with a Science, Technology, Engineering, and Math (STEM) approach. This research is Classroom Action Research (CAR). The subjects of this study were 34 students in class VII Semester 1 of 2022 at SMPN 6 Lembah Gumanti, Lembah Gumanti District, Solok Regency. This study consisted of 2 cycles with 4 stages, namely: planning, implementation, observation and reflection. Data collection techniques in this study are preliminary data, observations and written tests to measure scientific literacy skills in the form of knowledge (knowledge), competence (competences), and context (context) aspects collected using science literacy ability tests while attitude (attitudes) data is collected by using angket. Based on the results of the research carried out, the average score at cycle I was 67,06 and at cyclus II 85,88 so it can be concluded that the inquiry learning model with the STEM approach can improve student science literacy on environmental pollution materials